Morphology, rheology, properties, and applications of fullerene-filled polymer blends - Rasidi, Roslan; Mohd Hasbi, Ab Rahim (Elsevier, 2024)
In the last three decades, the utilization of fullerene's unique structure and characteristics rose steeply with interest from industries and academia. Numerous new fullerene derivatives have been developed, particularly involving fullerene incorporation into a polymer matrix. In this chapter, the essential properties for fullerene–polymer nanocomposites (fullerene-PNCs), which are morphology, rheology, mechanical, and thermal, are discussed. The most crucial factor, the morphology that affects the overall polymer performance, was elaborated. This includes the solvent suitability to disperse fullerene in the polymer matrix, the best polymer/fullerene ratio, the phase diagram of a binary polymer/fullerene system, and the effect of the domain size. The impact of fullerene incorporation on the viscosity changes, viscoelastic behavior, tensile strength, or fracture toughness is also discussed. Several applications related to fullerene-PNCs, such as commercial engineering thermoplastic, protective coating, and photovoltaic, are provided. Finally, a summary and outlook of fullerene-PNCs are presented.